A preparation method and application of nitrogen-doped porous carbon using highland barley straw

By using barley straw, activation agents KOH and TMAOH, nitrogen-doped porous carbon K-thAC adsorbent is prepared, which solves the problem that barley straw cannot effectively prepare high-efficiency adsorbent in the prior art, and achieves efficient adsorption performance on gasoline.

CN116832778BActive Publication Date: 2025-03-11NANJING INST OF ENVIRONMENTAL SCI MINIST OF ECOLOGY & ENVIRONMENT OF THE PEOPLES REPUBLIC OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310964386.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-03-11
Estimated Expiration
2043-08-02

AI Technical Summary

Technical Problem

The prior art is difficult to effectively use barley straw to prepare efficient nitrogen-doped porous carbon adsorbents, especially in adsorbing gasoline.

Method used

A nitrogen-doped porous carbon K-thAC adsorbent was prepared by a two-step activation method using barley straw as raw materials, combined with KOH and tetramethylammonia hydroxide (TMAOH) as activation agents.

Benefits of technology

The prepared K-thAC adsorbent exhibits excellent gasoline steam adsorption performance, has a large adsorption amount and good adsorption kinetics, and is simpler than other nitrogen doping methods and has less energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116832778B_ABST
    Figure CN116832778B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a nitrogen-doped porous carbon (K-thAC) adsorbent using highland barley straw as a raw material. The method comprises two steps: using KOH and TMAOH as activation agents, a nitrogen-doped layered porous carbon K-thAC adsorbent is activated and synthesized by a two-step method; K-thAC has a high specific surface area and a large pore volume, which are 3119 m 2 / g and 2.27 cm 3 / g, with a hierarchical pore structure with micro-meso-macroporous distribution; dynamic adsorption test shows that the saturated adsorption capacity of K-thAC for gasoline vapor is as high as 501 mg / g; the K-thAC adsorbent synthesized by the present invention has good gasoline vapor adsorption performance, especially has the remarkable characteristics of large saturated adsorption capacity, and also has the remarkable advantages of simple raw materials and low cost of activation agents, simple synthesis method, adjustable structure, etc., and can be used as a competitor of high-efficiency VOCs adsorbent in industry; TMAOH has broad prospects for AC activation due to its low addition concentration, mild conditions and high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon-based materials and novel adsorbents, and relates to a nitrogen-doped porous carbon adsorption material, specifically a preparation method for preparing nitrogen-doped porous carbon by utilizing highland barley straw and an application thereof. Background Art

[0002] With the acceleration of urbanization and the continuous expansion of urban scale in my country, traditional fuel vehicles have aggravated the pollution of volatile organic compounds (VOCs) in urban atmosphere. In particular, VOCs have significant effects on human health, and aggravate the greenhouse gas effect and the production of photochemical smog, which deteriorates the urban atmospheric environment and poses a risk of harm to human health. Therefore, effectively reducing and controlling VOCs including gasoline in cities and controlling ozone generation has become one of the environmental problems that my country urgently needs to solve. Adsorption technology has significant advantages in controlling VOCs pollution such as gasoline, such as low price, and has become one of the focuses of extensive research attention.

[0003] Activated carbon materials usually have a large specific surface area, a developed pore structure, and rich surface chemical groups. Due to their significant advantages such as low cost, they have become one of the commonly used excellent adsorbents. They have great utilization value and show good application prospects in the fields of volatile organic compound treatment, anti-toxicity and deodorization. The raw materials for industrial preparation of activated carbon mainly include sawdust, wood chips, coal, coconut shells and polymers (Carbon, 1998, 36(7): 1085-1097.), and potassium hydroxide (KOH) is a commonly used activator. my country is a traditional agricultural country. The use of agricultural waste resources to prepare activated carbon avoids the negative impact of incineration and landfill treatment on resources and environment, and can also turn agricultural waste into treasure for environmental pollution control, which has attracted widespread attention from scholars (Polymer Bulletin, 2021(7): 33-42.). As an agricultural waste in the Qinghai-Tibet Plateau, highland barley stalks have the characteristics of large output and cheap raw material prices. In particular, a large amount of highland barley stalks are treated as garbage every year. Incineration or landfill will cause great waste of resources and pollute the environment. There are few reports on the use of highland barley stalks as raw materials for the preparation of activated carbon. Literature search found that Zhang Shengming used ZnCl2 chemical activation method to prepare activated carbon with a specific surface area of ​​914.7 m 2 / g of activated carbon, and optimized the best process conditions affecting pore formation in the activated carbon preparation process to "activation temperature 600°C, impregnation rate 250% and activation time 60 minutes" (Qinghai Science and Technology, 2008, 5, 38-39). The theoretical knowledge of using highland barley straw to prepare activated carbon needs to be further improved and standardized. How to regulate the pore structure and specific surface area of ​​activated carbon adsorbent prepared from highland barley straw is one of the hot topics that academic research and industry should pay attention to. In addition, no relevant research reports on the use of highland barley straw to prepare nitrogen-doped porous carbon for gasoline adsorption have been retrieved. Summary of the invention

[0004] In order to solve the above problems, the present invention uses highland barley straw as raw material, KOH and tetramethylammonium hydroxide (TMAOH) as activation agents, and synthesizes nitrogen-doped porous carbon K-thAC adsorbent through a two-step activation method.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] The present invention provides a method for preparing nitrogen-doped porous carbon K-thAC by using highland barley straw, comprising the following steps:

[0007] (1) Wash and dry the highland barley straw, cut it into small pieces of 10-15 cm, and carbonize it in an inert gas atmosphere to obtain preliminary carbon;

[0008] (2) Under an inert gas atmosphere, the preliminary carbon is mixed with potassium hydroxide and activated at high temperature, then naturally cooled under an inert gas atmosphere, washed with 0.5N hydrochloric acid and purified water until neutral, and finally dried at 100-120 °C for 10-15 h to obtain an activated carbon K-AC adsorbent;

[0009] (3) The activated carbon K-AC was mixed with tetramethylammonium hydroxide solution, stirred at 1200 r / min for reaction, filtered and washed with pure water, and then dried at 100-120°C for 10-15 h to obtain a nitrogen-doped porous carbon K-thAC adsorbent.

[0010] Furthermore, in step (1), the carbonization temperature is 450-550°C, and the carbonization time is 1.5-2.5 h.

[0011] Furthermore, in step (1), the inert gas is argon.

[0012] Furthermore, in step (2), the mass ratio of the preliminary carbon to potassium hydroxide is 1:2-1:5, and the inert gas is argon.

[0013] Furthermore, in step (2), the high temperature activation conditions include: maintaining at 300-400°C for 1.5-3.5 hours, and then heating to 800-900°C and maintaining for 2.5-3.5 hours.

[0014] Furthermore, in step (3), the mass concentration of the tetramethylammonium hydroxide solution is 1%-25%.

[0015] Furthermore, in step (3), the mass volume ratio of the activated carbon K-AC to tetramethylammonium hydroxide is 1:15-1:25 g / ml.

[0016] Furthermore, in step (3), the activated carbon K-AC is mixed with tetramethylammonium hydroxide solution, and stirred at 20-30°C and 1200 r / min for 18-25 h.

[0017] The present invention also provides an application of the nitrogen-doped layered porous carbon prepared by the preparation method as described above in an adsorption material, wherein the application includes adsorbing gasoline.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention uses highland barley straw and active agents (KOH and TMAOH) to synthesize nitrogen-doped porous carbon K-thAC adsorbent through pyrolysis reaction. Studies have confirmed that K-thAC adsorbent has excellent gasoline vapor adsorption performance, and has significant characteristics such as large adsorption capacity and good adsorption kinetics; in addition, the present invention proves for the first time that tetramethylammonium hydroxide is an excellent nitrogen-doping agent.

[0020] Through the activation of tetramethylammonium hydroxide under relatively mild conditions, active groups can be effectively introduced on the surface of activated carbon. Combined with KOH and its own hydroxyl groups, it can play a good role in etching pores and introducing electron-rich groups. Moreover, it is simpler and consumes less energy than other nitrogen doping methods.

[0021] The K-thAC adsorbent prepared by the present invention has a maximum specific surface area and pore volume of 3119 m 2 / g and 2.27cm 3 / g, and the maximum saturated adsorption capacity for gasoline is 501 mg / g. Compared with most industrial activated carbons, K-thAC adsorbent has significant advantages in adsorbing gasoline vapor.

[0022] K-thAC is a nitrogen-doped porous carbon adsorbent. The nitrogen element in TMAOH can successfully replace the carbon or oxygen atoms in the intermediate product under room temperature and stirring conditions, laying the elemental foundation for the subsequent nitrogen doping reaction. During the activation reaction, TMAOH with strong alkalinity can provide electrons and selectively etch the original pores under looser reaction conditions, making the micropores and mesopores on the surface of the adsorbent precursor more abundant and the proportion of macropores significantly less, which can provide a mass transfer channel with a layered porous structure for the effective mass transfer of gasoline molecules.

[0023] The K-thAC synthesized by the present invention has good adsorption performance for gasoline vapor, and has the advantages of large adsorption capacity, excellent adsorption kinetics, etc. In particular, K-thAC has significant advantages such as low cost of raw materials and active agents, simple synthesis method, and adjustable pore size distribution, and can be used as an industrial substitute for efficient adsorption of VOCs. Secondly, the outstanding feature of low-concentration TMAOH being able to efficiently activate K-thAC under mild conditions has a broad application prospect for AC activation. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a static adsorption diagram of the nitrogen-doped porous carbon K-thAC prepared in Example 1 of the present invention;

[0025] Figure 2 This is a SEM comparison diagram of K-AC and K-thAC-10 prepared in Example 2 of the present invention;

[0026] Figure 3 This is an infrared FTIR comparison diagram of K-AC and K-thAC-1 prepared in Example 2 of the present invention;

[0027] Figure 4 XRD comparison diagram of K-AC and K-thAC-1 prepared in Example 2 of the present invention;

[0028] Figure 5 This is a dynamic adsorption diagram of the nitrogen-doped porous carbon K-thAC prepared in Example 1 of the present invention. Implementation

[0029] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Example 1

[0030] The preparation method of nitrogen-doped porous carbon K-thAC specifically comprises the following steps:

[0031] (1) Highland barley straw comes from the Qinghai-Tibet Plateau. The highland barley straw is washed with pure water and dried, cut into small pieces of 10-15 cm, and carbonized in an argon atmosphere at 500 °C for 2 h to obtain preliminary carbon.

[0032] (2) Under argon atmosphere, 1 g of preliminary carbon was mixed evenly with 2 g, 5 g, and 7 g of potassium hydroxide (carbon-base ratio was 1:2, 1:5, and 1:7, respectively), activated at high temperature (350 °C for 2 h, 850 °C for 3 h), and then naturally cooled under argon atmosphere. After that, it was washed with 0.5 N hydrochloric acid and pure water until neutral, and dried at 110-120 °C for 12 h to obtain a series of activated carbon K-AC;

[0033] Static adsorption rate detection method: The sample is heated in a 200 ℃ N2 flow for 2 h to remove impurities, and then cooled to 25 ℃ for use. Place 25 ml of gasoline sample at the bottom of the static adsorption device and let it stand for 5 minutes to allow the gasoline vapor to fill the inside of the device. Take 0.1 grams of sample into small cups in 5 identical devices. Place the entire device in a constant temperature water bath and maintain it at 298 K. Take out a sample at 15, 30, 60, 90, and 120 minutes to weigh the mass change and record the data. The static adsorption rate is calculated according to the following formula (1):

[0034] (1)

[0035] k1 represents the static adsorption rate, m1 is the carbon weight when the adsorption time is the selected time, and m0 is the carbon weight when the adsorption time is 0.

[0036] The static adsorption rate of a series of nitrogen-doped porous carbon K-AC obtained in this embodiment was tested respectively, and the better activated carbon K-AC was selected by comparing the different activation conditions of step (2) and performing the next step of activation. As shown in Table 1, the K-AC prepared with a carbon-base ratio of 1:7 and an activation temperature of 850°C has the best static adsorption rate. Compared with the activated carbon prepared by activation at 850°C, the pores of the activated carbon prepared at 750°C are not fully developed, especially some of the pores are not fully developed or are still blocked by substances such as coal tar. The activated carbon prepared at 900°C has serious corrosion of micropores, mesopores and micropores, and an increase in the number of macropores, resulting in a decrease in specific surface area and a decrease in the adsorption capacity of the material. In short, the carbon yield increases with decreasing temperature and increasing carbon-base ratio. However, whether it is 750°C, 850°C or 900°C, the carbon yield is very low when the carbon-base ratio is 1:7. Therefore, we comprehensively considered factors such as efficiency, energy consumption, and activator consumption, and evaluated the comprehensive performance of a certain carbon adsorbent according to formula (2). The results are shown in Table 1 below.

[0037] (2)

[0038] Among them, ω represents the comprehensive performance, k is the static adsorption rate of activated carbon at 120 min, α is the carbon-base ratio, T is the corresponding activation temperature, and 1000 is a constant.

[0039] Table 1 Static adsorption efficiency of activated carbon K-AC under different temperatures and activation ratios

[0040]

[0041] It can be seen from the above table that when the activation temperature is 850 °C and the carbon-alkali ratio is 1:5 and 1:2, the activated carbon K-AC has better comprehensive performance in adsorption efficiency and carbon yield; when the carbon-alkali ratio is 1:5, the activated carbon K-AC has the best adsorption efficiency and carbon yield. Therefore, implementation 2 selects this condition to prepare K-AC for the next step of activation. Example 2

[0042] The preparation method of nitrogen-doped porous carbon K-thAC specifically comprises the following steps:

[0043] (1) Highland barley straw comes from the Qinghai-Tibet Plateau. The highland barley straw is washed with pure water and dried, cut into small pieces of 10-15 cm, and carbonized in an argon atmosphere at 500 °C for 2 h to obtain preliminary carbon.

[0044] (2) Under argon atmosphere, 1 g of preliminary carbon was mixed with 5 g of potassium hydroxide (1:5) and activated at high temperature (350 °C for 2 h and 850 °C for 3 h), then naturally cooled under argon atmosphere, washed with 0.5 N hydrochloric acid and pure water until neutral, and dried at 100-110 °C for 12 h to obtain activated carbon K-AC;

[0045] (3) 1 g of activated carbon K-AC was mixed with 20 g of tetramethylammonium hydroxide aqueous solution, where the concentrations of tetramethylammonium hydroxide aqueous solution were 1%, 5%, 10% and 25%, respectively; the mixture was stirred at 1200 r / min at 20-30 ℃ for 24 h, filtered, washed with water, and then dried at 100-110 ℃ for 12 h to obtain a series of nitrogen-doped porous carbon K-thAC, which were labeled as K-thAC-1, K-thAC-5, K-thAC-10 and K-thAC-25, respectively.

[0046] K-thAC-1, K-thAC-5, K-thAC-10 and K-thAC-25 were subjected to static adsorption tests respectively. The test methods were the same as those in Example 1. The test results are shown in FIG. Figure 1 As shown. Figure 1 It can be seen that all nitrogen-doped porous carbons basically reached adsorption saturation at 20 min; and from the evaluation of the adsorption rate of the whole process, the high concentration of tetramethylammonium hydroxide activated K-AC can increase the adsorption rate again in the later period. The rapid increase in adsorption rate in the first period (0-30 min) is attributed to the physical adsorption of K-AC, while the increase in adsorption rate in the second half is attributed to the chemical adsorption process of functional groups on the carbon frame.

[0047] Dynamic adsorption rate detection method: the sample is heated in a N2 flow at 200 °C for 2 h to remove impurities. Cool to 25 °C; take 0.2 g of sample and place it in a glass tube of a dynamic adsorption device; open the pressure reducing valve and pass argon gas into the device at a rate of 100 ml / min for 5 min; then adjust the gas flow to 40 ml / min, turn the valve, and pass the gas into the bubbling device; from the beginning of the bubbling time, 50 s is the interval, and each gas collection bag collects gas for 15 s until 1000 s, and then dilutes 500 times in sequence; use a gas chromatograph to test the concentration of non-methane total hydrocarbons to draw an adsorption-breakthrough curve.

[0048] The dynamic adsorption rate k1 is calculated according to formula (3), where k1 represents the dynamic adsorption ratio, C is the instantaneous adsorption rate at the corresponding moment, and C0 is the maximum adsorption amount;

[0049] (3)

[0050] K-AC, K-thAC-1, K-thAC-5, K-thAC-10, and K-thAC-25 were subjected to dynamic adsorption tests, such as Figure 5 As shown, in the dynamic adsorption experiment, K-thAC showed good adsorption performance. The adsorption capacity of K-thAC activated by tetramethylammonium hydroxide was significantly improved compared with that of unactivated K-AC, and the higher the concentration, the more obvious the performance improvement. The data of the dynamic adsorption experiment was put into the formula for calculation, and the formula is as follows:

[0051] (4)

[0052] q e Indicates material adsorption t n Indicates the time corresponding to the sampling point (min); C n Indicates the detected concentration at the corresponding time (mg / m 3 ); 40 is the carrier gas flow rate (ml / min), 10 6 is the unit conversion constant.

[0053] According to formula (4), the maximum saturated adsorption capacity of gasoline by different K-thAC adsorbents reaches 501 mg / g.

[0054] K-AC, K-thAC-1, K-thAC-5, K-thAC-10 and K-thAC-25 were subjected to BET detection respectively, and the specific surface area and porosity of the corresponding materials are shown in Table 2. It can be seen from Table 2 that after adding TMAOH, the specific surface area increases and the porosity increases.

[0055] Table 2 Specific surface area and porosity of materials prepared in Example 2

[0056]

[0057] The activated carbon K-AC obtained in step (2) and K-thAC-10 obtained in step (3) were characterized by SEM. The characterization results are shown in Figure 2 .like Figure 2 As shown in the left figure, KOH etching of K-AC causes a large number of micropores below 2 nm to appear in the prepared activated carbon, and the volume of micropores below 2 nm is the most important factor affecting the adsorption performance of various adsorbents. In particular, when the size of activated carbon micropores is similar to the dynamic diameter of a certain volatile organic compound, the micropores have a larger adsorption energy.

[0058] Depend on Figure 2 From the right picture, we can see that a large number of pore structures can be observed in the activated carbon at low magnification, and TMAOH with obvious white dot structures is attached to the surface of the material.

[0059] The obtained K-AC and K-thAC-1 were detected by infrared spectroscopy, such as Figure 3 As shown,

[0060] Depend on Figure 3 It can be seen that after activation with tetramethylammonium hydroxide, even at very low concentrations, the groups of activated carbon still undergo significant changes, with the peaks at 2300 to 3100 cm -1 The range is such that 2990 cm -1 and 2873 cm -1 The increase of -CH2- functional groups and other carbon-containing functional groups at 2210 cm -1 The RC≡HR functional group at 1985 cm -1 The -C=C=C- accumulated double bond region appears at 1050 cm -1 The ester bond at 1542cm is weakened and disappears. It can be inferred that the ester bond undergoes alkaline hydrolysis in tetramethylammonium hydroxide aqueous solution. The ester bond is a polar functional group, which is not conducive to oil and gas absorption. - The peak at is -O-NH-, which is speculated to be a nitro compound group. After the TMAOH reaction, the response of aliphatic nitro compounds is significantly enhanced, and the adsorption of VOCs is enhanced.

[0061] The crystallinity of K-AC and K-thAC-1 samples was studied by XRD. Figure 4) show that K-AC and K-thAC-1 have two inconspicuous broad peaks of different intensities near 2θ=24° and 2θ=43°. These two weak diffraction peaks can be attributed to the (002) and (100) planes in the graphitic carbon structure, respectively. For the NPCK-x sample, the intensity of the peak at 2θ=24° weakens with the introduction of tetramethylammonium hydroxide. It is worth noting that for K-thAC-1, the broad diffraction peak at 2θ=43° almost disappears, indicating that the degree of graphitization of the carbon material is reduced after the introduction of tetramethylammonium hydroxide. These results indicate that after the use of tetramethylammonium hydroxide, the carbon material is more amorphous and more conducive to the adsorption of gasoline vapor than the material without tetramethylammonium hydroxide.

[0062] It should be noted that the above content only illustrates the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.

Claims

1. A two-step method for preparing nitrogen-doped porous carbon, characterized in that: The following steps are involved: (1) Wash and dry the highland barley straw, cut it into small pieces of 10-15 cm, and carbonize it in an inert gas atmosphere to obtain preliminary carbon; (2) In an inert gas atmosphere, the preliminary carbon is mixed with potassium hydroxide, and then activated at high temperature, and then naturally cooled in an inert gas atmosphere, and then washed with 0.5 N hydrochloric acid and pure water to neutrality, and dried at 100-120 ° C for 10-15 h to obtain activated carbon K-AC; (3) Mixing activated carbon K-AC with tetramethylammonium hydroxide solution, stirring at 1200 r / min, filtering and washing with pure water, and then drying at 100-120 °C for 10-15 h to obtain nitrogen-doped porous carbon; In step (3), the activated carbon K-AC is mixed with tetramethylammonium hydroxide solution, and stirred at 20-30°C and 1200 r / min for 18-25 h.

2. The method for preparing nitrogen-doped porous carbon by two-step synthesis according to claim 1, characterized in that: In step (1), the carbonization temperature is 450-550°C, and the carbonization time is 1.5-2.5 h.

3. The method for preparing nitrogen-doped porous carbon by two-step synthesis according to claim 1, characterized in that: In step (1), the inert gas is argon.

4. The method for preparing nitrogen-doped porous carbon by two-step synthesis according to claim 1, characterized in that: In step (2), the mass ratio of the preliminary carbon to potassium hydroxide is 1:2-1:5, and the inert gas is argon.

5. The method for preparing nitrogen-doped porous carbon by two-step synthesis according to claim 1, characterized in that: In step (2), the high temperature activation conditions include: maintaining at 300-400°C for 1.5-3.5 h, then heating to 800-900°C and maintaining for 2.5-3.5 h.

6. The method for preparing nitrogen-doped porous carbon by two-step synthesis according to claim 1, characterized in that: In step (3), the mass concentration of the tetramethylammonium hydroxide solution is 1%-25%.

7. The method for preparing nitrogen-doped porous carbon by two-step synthesis according to claim 1, characterized in that: In step (3), the mass volume ratio of the activated carbon K-AC to the tetramethylammonium hydroxide solution is 1:15-1:25 g / mL.

8. Use of nitrogen-doped porous carbon prepared by the preparation method according to any one of claims 1 to 7 in adsorption materials, characterized in that: The applications include the adsorption of gasoline.